Effect of alvimopan on accelerates gastrointestinal recovery after radical cystectomy: A systematic review and meta-analysis. (January 2016) - Cui, Yu; Chen, Hequn; Qi, Lin; Zu, Xiongbing; Li, Yang
Abstract: Purpose: The aim of the study was to evaluate the efficacy of alvimopan on accelerates gastrointestinal recovery after radical cystectomy. Methods: We searched for all studies investigating alvimopan for bladder cancer patients undergoing radical cystectomy in Pubmed, Web of Knowledge, and the Cochrane Central Search Library. A systematic review and meta-analysis were performed. All studies that compared alvimopan with control group for patients undergoing radical cystectomy were included. Studies with overlapping or insufficient data were excluded. No language restrictions were made. Efficacy was assessed by the time to first toleration of clear liquids, first toleration of solid food, first bowel movement and length of stay. Results: Our searches identified 5 studies, including 613 patients. A total of 294 (47%) patients took alvimopan. On meta-analysis, alvimopan reduced time to first toleration of clear liquids (HR 1.34, 95% CI 1.19 to 1.51, p < 0.001), first toleration of solid food (HR 1.22, 95% CI 1.11 to 1.34, p < 0.001), first bowel movement (HR 1.27, 95% CI 1.12 to 1.43, p < 0.001) and length of stay (HR 1.17, 95% CI 1.10 to 1.25, p < 0.001). Conclusions: This meta-analysis has shown that alvimopan significantly accelerates recovery of gastrointestinal function and reduces the length of stay in patients performed radical cystectomy. More large scale, multicenter randomized controlled studies are needed before final clinical recommendations can be made. Highlights: Intestinal related complications are common in the patients undergoing radical cystectomy. Alvimopan significantly accelerates recovery of gastrointestinal function in patients performed radical cystectomy. Alvimopan reduces the length of stay after radical cystectomy.